Idiopathic portal hypertension associated with cytotoxic drugs. Issue 3 (March 1990) - Shepherd, P; Harrison, D J
Abstract : Four patients developed clinically important portal hypertension with histological features of idiopathic portal hypertension while they were receiving cytotoxic drugs for chronic myeloid leukaemia and Hodgkin's disease. Mild sclerosis of some small portal triads was the only abnormality seen at light microscopical examination in three of the four cases. In the remaining case light microscopical findings seemed to be normal. Two cases examined by electron microscopy showed perisinusoidal fibrosis; in one case this was the only abnormality detected. There is an association between idiopathic portal hypertension and the use of chemotherapeutic agents, particularly thioguanine. Adequate histological examination of liver tissue, including electron microscopic studies, is recommended for patients who develop hepatic problems while receiving cytotoxic treatment to elucidate this problem.